2017
DOI: 10.18632/oncotarget.22413
|View full text |Cite
|
Sign up to set email alerts
|

Renal oncocytoma characterized by the defective complex I of the respiratory chain boosts the synthesis of the ROS scavenger glutathione

Abstract: Renal oncocytomas are rare benign tumors of the kidney and characterized by a deficient complex I (CI) enzyme activity of the oxidative phosphorylation (OXPHOS) system caused by mitochondrial DNA (mtDNA) mutations. Yet, little is known about the underlying molecular mechanisms and alterations of metabolic pathways in this tumor. We compared renal oncocytomas with adjacent matched normal kidney tissues on a global scale by multi-omics approaches, including whole exome sequencing (WES), proteomics, metabolomics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(77 citation statements)
references
References 97 publications
(130 reference statements)
13
58
1
Order By: Relevance
“…Multi-omics profiling of pRCC was performed, revealing a fundamental reprogramming of the pathways for gluconeogenesis, the respiratory chain, and for glutathione metabolism. These can be regarded as a general hallmark of kidney tumors, as was previously observed in renal oncocytomas (17), chRCCs (27), and in ccRCCs at the transcript level (28).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Multi-omics profiling of pRCC was performed, revealing a fundamental reprogramming of the pathways for gluconeogenesis, the respiratory chain, and for glutathione metabolism. These can be regarded as a general hallmark of kidney tumors, as was previously observed in renal oncocytomas (17), chRCCs (27), and in ccRCCs at the transcript level (28).…”
Section: Discussionmentioning
confidence: 59%
“…In our previous study on renal oncocytomas, we identified a coordinated up-regulation of proteins of the OXPHOS complexes II-V and the mtDNA, but a striking reduction in the abundance of CI proteins ( Figure 3A) (17). This was explained by several specific low-level heteroplasmic mtDNA mutations of the CI genes in renal oncocytomas.…”
Section: Malignant Prcc and Benign Renal Oncocytomasmentioning
confidence: 71%
See 1 more Smart Citation
“…28 Multi-compartment models and models based on partial differential equations are available to compute the distribution and excretion of substances such as FDG, 33 drugs, 34,35 glucose and lactate 36 and to describe the regulation of renal salt and water excretion, glomerular blood flow, filtration rates and blood flow. 39 , represents an efficient way to generate metabolic cell models that can be integrated into existing tissue-scale models of the kidney. Similar to the liver, renal epithelial enzyme patterns vary considerably, including reciprocal capacities of gluconeogenesis and glycolysis in tubule cells resident in the cortex and the medulla.…”
mentioning
confidence: 99%
“…38 Owing to the high similarities shared between the central metabolism of hepatocytes and renal tubule cells, re-parameterization of complex kinetic liver models 14 with kidney-specific parameters, as has been done in Ref. 39 , represents an efficient way to generate metabolic cell models that can be integrated into existing tissue-scale models of the kidney.…”
mentioning
confidence: 99%